Improved wireless LED-based light emitters for photocatalytic oxidation in a slurry annular reactor - Aziz, Zulkifly; Mohd Mawardi, Saari; Mohd Aufa Hadi Putera, Zaini; Nurul A’in, Nadzri; Chin, S. Y. (SIGMA BOT, 2023)
In this work, a custom-built ferrite rod was designed to replace the commercial ferrite drum core in a conventional wireless light emitter driven by wireless power transfer for photocatalytic oxidation of wastewater. Simultaneous improvement in coupling coefficient and quality factor was achieved, allowing maximum energy transfer. A coupling coefficient of 0.024 was achieved at the center of the field coil at zero angular misalignment for a coil quality factor of 74 measured at the switching frequency of 185 kHz. In addition, the emitter irradiation intensity could be regulated from 80 – 380 W/m2, a useful feature in the situation where high intensity promotes the recombination of electrons and holes.